A finite element analysis of bolted joints loaded in tension: protruding head and countersunk fastener. Issue 1 (6th February 2017) - Dursun, Tolga; Soutis, Costas
Abstract : Purpose: The purpose of this paper is to investigate the effect of fastener geometry (protruding head and countersunk fastener) and friction coefficient on the stress distributions around the hole of the double-lap single bolted aluminium alloy joints. Design/methodology/approach: 3D finite element analyses of double-lap bolted 7075-T6 aluminium joints were carried out. An elastic-plastic multi-linear kinematic hardening material behaviour was assumed for the Al alloy. Contact was defined using an augmented-Langrange contact algorithm, including the friction effect. Bolt clamping force and remote axial tensile loading were applied in two load steps and their separate and combined effects on the joint behaviour were investigated for two types of fastener configurations. Findings: It was observed that bolt clamping reduces the axial tensile stress at the hole edge by introducing a through-thickness compressive stress. This reduction in stress concentration may have a beneficial effect on the fatigue life of the joint. Second, bolt clamping reduces the bearing stress at the fastener hole by creating a frictional force between the joint plates. Results showed that the joint with protruding head fastener shows lower tensile stress concentration, and lower bearing stress, near the bolt hole of the middle plate. Originality/value: Bolt clamping force reduces both the stress concentration near the hole edge and the bearing stress at the hole by creating a frictional force. Joint with a protruding head fastener may lead to higher load carrying capability and improved fatigue life. Friction coefficient affects the stress levels around the bolt hole.